Fight to Win! Tools for Confronting Capital - Jeffrey Monaghan; David Troy Cochrane (In The Accumulation of Freedom: Writings on Anarchist Economics, 2012)
Anarchists have generally rejected the idea that there is or ought to be a pure or inherently revolutionary strategy or tactic. In this chapter we make use of the capital-as-power theory of value and capital in a way that informs and supports the ad hoc perspective on struggle and fighting to win. Our primary purpose is to propose a method based on this theory as a means for social justice activists to assess political-economic disruption campaigns (PEDCs). Such an analysis is a needed component of an anarchist economics.
Keywords: P16; P26; P48; Q34; 330; activism; anarchism; capital as power; political-economic disruption campaigns (PEDCs)